LITERASI AGAMA PADA ANAK MELALUI PROGRAM PEMBIASAAN PRAKTIK IBADAH - Khulusinniyah Khulusinniyah; Moh. Zamili (Fakultas Tarbiyah, Universitas Ibrahimy, 2021)
religious literacy of children can be started from studying the religious doctrine correctly. These activity of religious literacy can be implemented for children by performing a program of habituating worship practices in early childhood education institutions. The implementation of this habituation program must be planned clearly and always evaluated. In its implementation, teachers and children demonstrate directly so that it is known correctly the kaifiyat of worship by Islamic doctrine. The main target of this program of practicing worship habituation is that children able to and regularly performing worship as a necessity of daily life.